2017
DOI: 10.5603/fhc.a2017.0012
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations in the jejunal mucosa of aged rats and the possible protective role of green tea

Abstract: introduction. Gastrointestinal disorders become more prevalent with ageing. This study is aimed to describe morphological changes that occur in the jejunal mucosa of male albino rats as a result of ageing and the protective effect of green tea (GT) extract. Material and methods. The experiment was performed on sixty rats: thirty young-adult (6-month old, body mass 200-220 g) and thirty old (24-month-old, body mass 220-260 g) animals. Each group was further divided into two subgroups (n = 15 each): control rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In an experiment performed on the mice at 3 different ages (3-mo-old, 12-mo-old, and 24-mo-old), it has been identified that thinner mucosal muscularis, shortened and scattered villus, and reduced villus density can be observed from the ileal histological structure in the aging mice, which may be related to the mucosal atrophy, increased bacteria counts, and decreased expression of epithelial tight junction proteins ( Ren et al., 2014 ). Similarly, another report has also demonstrated that 24-mo-old rats exhibit the distorted and destructed state of jejunum, as well as the disrupted mucosal antioxidant defense system ( Hassan et al., 2017 ), suggesting the negative effects of aging on gut function. In humans, a literature has summarized that aging is accompanied by the continuous damage to morphology and function of gastrointestinal tract, which would impair the nutrient absorption and protection against ingested pathogens ( Soenen et al., 2016 ).…”
Section: Introductionmentioning
confidence: 87%
“…In an experiment performed on the mice at 3 different ages (3-mo-old, 12-mo-old, and 24-mo-old), it has been identified that thinner mucosal muscularis, shortened and scattered villus, and reduced villus density can be observed from the ileal histological structure in the aging mice, which may be related to the mucosal atrophy, increased bacteria counts, and decreased expression of epithelial tight junction proteins ( Ren et al., 2014 ). Similarly, another report has also demonstrated that 24-mo-old rats exhibit the distorted and destructed state of jejunum, as well as the disrupted mucosal antioxidant defense system ( Hassan et al., 2017 ), suggesting the negative effects of aging on gut function. In humans, a literature has summarized that aging is accompanied by the continuous damage to morphology and function of gastrointestinal tract, which would impair the nutrient absorption and protection against ingested pathogens ( Soenen et al., 2016 ).…”
Section: Introductionmentioning
confidence: 87%
“…Morphological changes in aged mouse and rat models have been described as thicker muscular layers, distorted villi, more secretory Paneth and goblet cells, and impaired junctions between adjacent enterocytes [ 18 - 24 ]. Mice have wider and higher villi with increasing age [ 22 ], while rats have wider and shorter ones [ 23 ]. Furthermore, rats have darkly stained nuclei in their aged intestines [ 23 ].…”
Section: Age-related Changes In the Intestinementioning
confidence: 99%
“…Mice have wider and higher villi with increasing age [ 22 ], while rats have wider and shorter ones [ 23 ]. Furthermore, rats have darkly stained nuclei in their aged intestines [ 23 ]. Human studies showed no significant changes in the duodenum [ 25 ].…”
Section: Age-related Changes In the Intestinementioning
confidence: 99%
“…The intestinal tract comprises structurally and functionally distinct regions, including digestive, absorptive, secretory, and protective functions ( Bergin and Witzmann, 2013 ; Hassan et al, 2017 ). More than 100 trillion bacteria live in human digestive tracts and we collectively call them the gut microbiota ( van den Brule et al, 2016 ; Li et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%